Everolimus for the treatment of advanced, non-functional neuroendocrine tumours of the lung or gastrointestinal tract (RADIANT-4): a randomised, placebo-controlled, phase 3 study. Issue 10022 (5th March 2016) - Yao, James C; Fazio, Nicola; Singh, Simron; Buzzoni, Roberto; Carnaghi, Carlo; Wolin, Edward; Tomasek, Jiri; Raderer, Markus; Lahner, Harald; Voi, Maurizio; Pacaud, Lida Bubuteishvili; Rouyrre, Nicolas; et al.
Summary: Background: Effective systemic therapies for patients with advanced, progressive neuroendocrine tumours of the lung or gastrointestinal tract are scarce. We aimed to assess the efficacy and safety of everolimus compared with placebo in this patient population. Methods: In the randomised, double-blind, placebo-controlled, phase 3 RADIANT-4 trial, adult patients (aged ≥18 years) with advanced, progressive, well-differentiated, non-functional neuroendocrine tumours of lung or gastrointestinal origin were enrolled from 97 centres in 25 countries worldwide. Eligible patients were randomly assigned in a 2:1 ratio by an interactive voice response system to receive everolimus 10 mg per day orally or identical placebo, both with supportive care. Patients were stratified by tumour origin, performance status, and previous somatostatin analogue treatment. Patients, investigators, and the study sponsor were masked to treatment assignment. The primary endpoint was progression-free survival assessed by central radiology review, analysed by intention to treat. Overall survival was a key secondary endpoint. This trial is registered withClinicalTrials.gov, numberNCT01524783 . Findings: Between April 3, 2012, and Aug 23, 2013, a total of 302 patients were enrolled, of whom 205 were allocated to everolimus 10 mg per day and 97 to placebo. Median progression-free survival was 11·0 months (95% CI 9·2–13·3) in the everolimus group and 3·9 months (3·6–7·4) in the placebo group. Everolimus was associated with a 52% reduction in the estimated risk of progression or death (hazard ratio [HR] 0·48 [95% CI 0·35–0·67], p<0·00001). Although not statistically significant, the results of the first pre-planned interim overall survival analysis indicated that everolimus might be associated with a reduction in the risk of death (HR 0·64 [95% CI 0·40–1·05], one-sided p=0·037, whereas the boundary for statistical significance was 0·0002). Grade 3 or 4 drug-related adverse events were infrequent and included stomatitis (in 18 [9%] of 202 patients in the everolimus group vs 0 of 98 in the placebo group), diarrhoea (15 [7%] vs 2 [2%]), infections (14 [7%] vs 0), anaemia (8 [4%] vs 1 [1%]), fatigue (7 [3%] vs 1 [1%]), and hyperglycaemia (7 [3%] vs 0). Interpretation: Treatment with everolimus was associated with significant improvement in progression-free survival in patients with progressive lung or gastrointestinal neuroendocrine tumours. The safety findings were consistent with the known side-effect profile of everolimus. Everolimus is the first targeted agent to show robust anti-tumour activity with acceptable tolerability across a broad range of neuroendocrine tumours, including those arising from the pancreas, lung, and gastrointestinal tract. Funding: Novartis Pharmaceuticals Corporation.